Examination Malpractices as the Bane of Nigeria Education System: Implications for Educational Planning and Management - Oko, Orji Friday; Nguwasen, Mando Patricia; Ajaegbo, A. N. (American Journal of Education and Learning, 2017)
The study investigated examination malpractices as the bane of Nigeria education system with attention on its implications for educational planning and management. Descriptive survey design was adopted; population of the study consisted all lecturers in the 40 federal universities in Nigeria. Purposive sampling was used to select 24 universities and 2,400 lecturers across the 6 geopolitical zones in Nigeria. Three research questions guided the study while test-retest method in testing reliability of the instrument. The result of Pearson product moment correlation: r=0.84 and was considered satisfactory. Arithmetic Mean (X) was used for data analysis. The result showed that fear of failure, congested sitting arrangement in examination halls, ineffectiveness of lecturers, greed and corruption etc. are reasons why students and education implementer associate with examination malpractice. It was concluded that Examination malpractice of all kinds should be abhorred and discouraged irrespective of excuses as it leads to unproductive graduates.